Conditions of a controlled atmosphere for the storage of 'Laetitia' plums treated with 1-methylcyclopropene Condições de atmosfera controlada para armazenamento de ameixas 'Laetitia' tratadas com 1-metilciclopropeno - Tanaka H.* (2013)
The aim of this study was to evaluate the effect of controlled-atmosphere (CA) conditions, both when combined and not with an application of 1-MCP, on the ripening and quality maintenance of 'Laetitia' plums, especially on the incidence of flesh breakdown. The treatments evaluated were: T1 - 21 kPa O2 + <0.05 kPa CO2; T2 - 1 kPa O2 + 1 kPa CO2; T3 - 1 kPa O2 + 1 kPa CO2, com 1-MCP (1 μL L-1); T4 - 2 kPa O2 + 3 kPa CO2; T5 - 2 kPa O2 + 3 kPa CO2 com 1-MCP (1 μL L-1). After 60 days in storage (0.5 ± 0.1 °C and 96 ± 2% RH) and three more days at ambient temperature (20 ± 2 °C and 60 ± 5% RH), the fruits were assessed for the attributes: red-color index (RCI); flesh and skin colour; firmness; texture; titratable acidity; respiratory rate; ethylene-production and incidence of flesh breakdown. A tasting of the fruit was also carried out using an untrained panel of people. Storage under both of the CA conditions (1 kPa O2 + 1 kPa CO2 and 2 kPa O2 + 3 kPa CO2) delayed ripening of the 'Laetitia' plums but did not inhibit the incidence of breakdown. However, the AC conditions of 1 kPa O2 + 1 kPa CO2 associated with the 1-MCP reduced the intensity of browning and produced a greater acceptability of the fruit.